2017
DOI: 10.7326/m16-1432
|View full text |Cite
|
Sign up to set email alerts
|

High Generic Drug Prices and Market Competition

Abstract: None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 10 publications
8
51
1
3
Order By: Relevance
“…These findings contrast sharply with evidence presented by previous studies suggesting generic competition is significant, commonly involving four or more suppliers in the first 24 months after loss of patent protection and other exclusivities (Berndt and Aitken 2011;Berndt and Newhouse 2012). The research findings reported here are also generally consistent with recently published research based on selected claims data encompassing a more limited set of generic drug markets (Dave et al 2017).…”
Section: Discussionsupporting
confidence: 54%
“…These findings contrast sharply with evidence presented by previous studies suggesting generic competition is significant, commonly involving four or more suppliers in the first 24 months after loss of patent protection and other exclusivities (Berndt and Aitken 2011;Berndt and Newhouse 2012). The research findings reported here are also generally consistent with recently published research based on selected claims data encompassing a more limited set of generic drug markets (Dave et al 2017).…”
Section: Discussionsupporting
confidence: 54%
“…However, the relative price reduction of biosimilars might not be as profound as that of chemical generics, where competition between multiple manufacturers finally drives prices in a downward direction to more than 50% in most markets. 50,51 Because of the considerable costs associated with manufacturing, marketing, storage, and special requirements for pharmacovigilance, a greater time might be required to drive the cost savings effect of biosimilars until more biosimilars enter the market to cause a high level of market competition. 50 Nonetheless, a massive price reduction for biosimilars has been observed in various countries.…”
Section: Economic Issuesmentioning
confidence: 99%
“…50,51 Because of the considerable costs associated with manufacturing, marketing, storage, and special requirements for pharmacovigilance, a greater time might be required to drive the cost savings effect of biosimilars until more biosimilars enter the market to cause a high level of market competition. 50 Nonetheless, a massive price reduction for biosimilars has been observed in various countries. In Norway, CT-P13 enabled a cost reduction of 51%-65% compared to originator infliximab; in France, the price discount is 45%, and in Japan, the current price of CT-P13 is 67% lower than that of originator infliximab.…”
Section: Economic Issuesmentioning
confidence: 99%
“…We found that the mean annual cost of topical therapy for branded medications per person was nearly twice the cost of generics, despite the rise in generic drug costs. 4 Thus, there is an opportunity to save health care costs, which amount to nearly $7.5 million annually for this cohort. Importantly, we analyzed the data from a health care system point of view, which provides more realistic overall cost analysis and is different from a patient point of view, in which, for example, coupons and other discounts reduce immediate out-of-pocket expense but increase societal cost.…”
Section: Trends In Utilization Of Topical Medications For Treatment Omentioning
confidence: 99%